Implementation of the Backtracking Algorithm for Bandwidth Management in the Network of SMA Negeri 1 Belitang - Hafizena, M. Fachri; Sutabri, Tata (International Journal Scientific and Professional, 2025)
Internet has become an essential necessity in the field of education, particularly in supporting the teaching and learning processes in schools. Effective bandwidth management ensures efficient and equitable network usage for all users. This study implements the Backtracking algorithm as a solution for bandwidth management at SMA Negeri 1 Belitang. The algorithm is utilized to optimize bandwidth allocation based on usage priority and the dynamic number of users. The results indicate that this method can enhance bandwidth utilization efficiency, reduce delays, and improve the quality of service (QoS). Therefore, the Backtracking algorithm can serve as an alternative solution for achieving optimal network management in schools.